Ti3C2Tx solid lubricant coatings in rolling bearings with remarkable performance beyond state-of-the-art materials. (December 2021) - Marian, Max; Feile, Klara; Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Seynstahl, Armin; Tremmel, Stephan; Krauß, Sebastian; Merle, Benoit; Böhm, Thomas; Wang, Bo; Wyatt, Brian C.; et al.
Highlights: Multi-layer MXenes were used as solid lubricants coatings for rolling bearings. Comparison with molybdenum disulfide (MoS2 ) and diamond-like carbon (DLC) coatings. Bearing washer wear was substantially reduced by MXene coatings. Transfer film formation verified on secondary contacts (rolling elements/cage pockets). Service life extension by 30 and 55% compared to MoS2 and DLC, respectively. Abstract: Two-dimensional (2D) transition metal carbides, nitrides, and carbonitrides, known as MXenes, are a growing class of 2D materials, which offer great solid lubrication ability for low friction applications due to their weakly bonded multi-layer structure and tribo-layer formation with self-lubricating characteristics. To date, most studies have assessed their tribological response in basic laboratory tests. However, these tests do not adequately reflect the complex geometries, kinematics, and stresses present in machine components. Here, we aim at bridging this gap through assessment of the friction and wear performance of multi-layer Ti3 C2 T x MXene solid lubricant coatings used in rolling bearings. MXenes' tribological response is compared with state-of-the art solid lubricant coatings, which include molybdenum disulfide (MoS2 ), tungsten-doped hydrogenated amorphous carbon (a-C:H:W), and hydrogen-free, more graphite-like amorphous carbon (a–C). Multi-layer Ti3 C2 T x MXene coatings reduce wear on the bearing washers by up to 94%, which can be attributed to the transfer of the lubricious MXene nano-sheets to secondary tribo-contacts of the bearing. While the frictional torque of all solid lubricant coatings is similar during steady-operation, the MXene-coated bearings extend the service life by 30% and 55% compared to MoS2 and DLC, respectively. This contribution demonstrates the ability of MXene solid lubricant coatings to outperform state-of-the-art solid lubricants in dry-running machine components such as rolling bearings. Graphical abstract: Image, graphical abstract